How Does AI Support Population Health Management? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Population health management (PHM) is a critical component of modern healthcare, focusing on improving the health outcomes of a defined group of people. Howe...
Keywords: AI in Clinical Decision Support; Support; Population; Health; Artificial Intelligence; Healthcare